Smoke (Paul Auster et Wayne Wang, 1995) : une œuvre à la croisée des arts - Delphine Letort (Transatlantica)
The adaptation of the short story entitled “Auggie Wren’s Christmas Story” (1990) gathered the writer Paul Auster and the director Wayne Wang around a film project that allowed them to share their artistic practices in a collaborative work. This paper examines the question that underpins the narrative of the short-story by grappling with the appropriations of the real in other artistic modes. Paul Auster’s first encounter with the cinema points out the convergence between aural writing and cinematic writing, evoked through the double figure of the writer and that of the tale-teller/photographer in both the film and the short story.